Solanum muricatum Aiton Juice as A Hepatoprotective Agent in Wistar Rats Induced With Carbon Tetrachloride - Yang, Justine Sim Wei; Istriati, Istriati; Rostini, Tiene (Althea Medical Journal, 2015)
Background: Liver participates in various metabolic processes in human body. Exposures to toxins such as carbon tetrachloride (CCl4) results in hepatocyte destruction and release the cell contents. Enzymes such as serum glutamic pyruvic transaminase (SGPT) were used as a parameter to diagnose liver damage. Pepino (Solanum muricatum Aiton) contains antioxidants that protect liver from hepatoxicity. The aim of this experiment is to determine the effect of pepino in protecting the hepatocyte from hepatotoxic effect of CCl4.Methods: A total of 16 Wistar rats used as the subject were divided into Control and Therapeutic Group. The Control group was induced with CCl4 but was not given pepino juice. Meanwhile, the Therapeutic Group was given pepino juice for 10 days. For induction of hepatotoxicity, CCl4 10% was given at a dosage of 2.0 ml/kg intra-peritoneal. Each Wistar rat in Therapeutic Group was given 1.0 ml of 300 g/ml pepino juice via oral feeding. Spectrophotometer with adjusted wavelength of 340 nm was used to measure SGPT level of the Wistar rats and statistical T-test was used to analyze the data.Results: Wistar rats in Therapeutic group showed a larger decrease (6898.9 IU/Lâ79.1 IU/L) in SGPT level compared to the Control group (6469.8 IU/Lâ418.5 IU/L). The SGPT level of the Wistar rat in Therapeutic group reached normal baseline (50 IU/Lâ150 IU/L). The significance of the experiment was supported by the T-test, P-value <0.05Discussion: Pepino juice had antioxidants that protect the hepatocyte of Wistar rats from free radicals. The synergistic action of antioxidants and hepatocyte regeneration of Wistar rats in Therapeutic group caused a decrease in SGPT level. Therefore, the experiment concluded that pepino juice at the dosage of 300 g/ml has hepatoprotective effect.Key words: Carbon tetrachloride, hepatotoxicity, Pepino, Solanum muricatum Aiton, SGPTÂ DOI:Â 10.15850/amj.v2n4.484